Dilemmas and Perspectives of Financing Nepal’s School Education - Koirala, Matrika Prasad; Koirala, Amit (Academic Voices: A Multidisciplinary Journal, 2015)
When concerns are growing that the elementary education should be fundamental rights, the challenges with financing of education is getting deeper for Nepal. This paper tries to explore the possibilities of bearing educational cost by the state. As elementary education has been made compulsory and free in line with international commitments and theoretical concerns, but the financial provision are not equipped to address the commitments. The present programmes, actions, strategies and budgets mark gaps with each other and with the resources. The existing institutional mechanism does not convince to be optimistic even in near future. The only hope remains with a reform in an institutional set up with committed professionals who can adrenalize the educational governance, which is also full of challenges; or seek alternatives from the local society and early practices. DOI: http://dx.doi.org/10.3126/av.v4i0.12354 Academic Voices Vol.4 2014: 29-36